Relational Planning as a Collective Critical Inquiry. Socio-Environmental Justice, Critical Moments and Reflective Responses in Six Years of Studio Teaching - De Blust, Seppe; Van den Broeck, Pieter; Devos, Tim; Moulaert, Frank (Planning, practice & research, 2022)
This paper presents a practical and pedagogical model of socially innovative planning based on four dialectical relations between actors, institutions and planning instruments that frame, constitute and position planning actions. The paper illustrates and evaluates this model by analysing four spatial planning studios that took place during the authors' six-year long engagement in a heavily contested urban renewal project in the city of Antwerp, Belgium. The paper shows how a frame for critical inquiry helped to address changes in the studio and project realities. by understanding, experiencing and responding to the ethical and socio-environmental consequences of spatial planning practice.